Pengaruh Tingkat Pendapatan Keluarga Terhadap Kemiskinan Rumah Tangga - Sri Hartuti Ibrahim; Usman Moonti; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The research aims to determine the influence of family income level on household poverty in Talumopatu Village,tapa Sub-district,Bone Bolango regency. This research uses aquantitative approach with the descriptive method. The data used are primary data obtained from distributing questionnaires to the poor in Talumopatu Village, Tapa Sub-district, Bone Bolango Regency. The sampel includes 36 respondents.Data analysis uses simple linear regression. The results showed an influence of family income level on household poverty in Talumopatu Village, Tapa Sub-district, Bone Bolango Regency. The influence of family income level on household poverty was 23,5%, while the remaining 76,5% was explained by other variables not examined in this research